Multi-material 4D printing employing stimuli-responsive polymer composites using vat photopolymerization - Fahad Alam; Nazek El-Atab (Virtual and Physical Prototyping)
Vat photopolymerization presents a versatile platform for realising intricate 4D printed structures with dynamic functionalities. This study examines the use of the vat photopolymerization technique for 4D printing employing stimuli-responsive polymers via a novel multi-material printing approach. As a potential application, the feasibility of printing encryptions with distinct layers comprising different responsive materials is explored, enabling activation through a combination of two or three stimuli. High-resolution structures with well-defined interfaces between the materials can be realised by leveraging the precision and versatility of vat photopolymerization. Shape-memory polymer-based 4D printed encryption exhibits selective activation when exposed to specific thermal (40 °C) and UV-light stimuli (405 nm), showing potential for advanced information storage, anti-counterfeiting, and camouflage writing applications. These findings highlight the capability of the proposed approach using vat photopolymerization to fabricate complex, stimulus-responsive constructs, fostering innovative applications in adaptive systems and smart devices.